2016
DOI: 10.1177/1756283x15625584
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided FNA for biliary disease as first-line modality to obtain histological evidence

Abstract: Background: Few reports have described endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) for biliary lesions. In addition, adverse events were not completely examined in previous reports, due to the inclusion of cases in which biliary stents had already been placed. The present study aimed to investigate the diagnostic yield and adverse events of EUS-FNA for biliary lesions as the first-line diagnostic modality for consecutive prospectively registered patients. Methods: Inclusion criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Selection of modality being more cost‐effective as the initial diagnostic tool for biliary stricture or as a “rescue” method for indeterminate biliary strictures is largely unclear. However, it appears reasonable to combine different techniques within 1 procedure to maximise the diagnostic yield, reduce false‐negative results and the number of endoscopic procedures …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of modality being more cost‐effective as the initial diagnostic tool for biliary stricture or as a “rescue” method for indeterminate biliary strictures is largely unclear. However, it appears reasonable to combine different techniques within 1 procedure to maximise the diagnostic yield, reduce false‐negative results and the number of endoscopic procedures …”
Section: Resultsmentioning
confidence: 99%
“…It is considered appropriate to perform EUS‐FNA on distal bile duct lesions, unresectable biliary malignancies, or lesions causing extrinsic compression. A prospective study of 47 patients revealed that EUS‐FNA can be safely performed as a first‐line diagnostic modality for suspected cholangiocarcinoma with a satisfactory diagnostic sensitivity (89%) and accuracy (87%) . If initial EUS‐guide sampling proves nondiagnostic then a subsequent ERCP‐based intraductal tissue sampling can be taken.…”
Section: Resultsmentioning
confidence: 99%
“…EUS can provide many additional information and help stage the lesion, which is a determining factor for tumor ressectability 8 21 22 .…”
Section: Discussionmentioning
confidence: 99%
“…EUS-FNA’s sensitivity in biliary strictures is heterogeneous, varying from 46 % to 100 % 5 21 22 23 24 25 26 27 , and specifically for intraductal lesions between 53 % and 89 % 6 23 24 . Our study demonstrated good sensitivity for the method, with a sensitivity of 93.8 % on the global analysis, 100 % in extraductal lesions and 80 % in intraductal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using EUS-FNA as a safer alternative to ERCP was also investigated. For instance, Onda et al performed EUS-FNA as the first-line method in patients with suspected ECCA based on CT or other imaging modalities with sensitivity of 89% and accuracy of 87% [79]. In a recent meta-analysis, De Moura et al calculated the mean sensitivi-ties of ERCP and EUS-FNA for the tissue diagnosis of a malignant biliary stricture to be 49% and 75%, while specificities were 96% and 100% [80].…”
Section: Endoscopic Ultrasound Endoscopic Ultrasound (Eus)mentioning
confidence: 99%